Research of clover-grater-and-scarificator KS-0.2 with oval type deck at seeds scarification - A. I. Burkov; M. V. Simonov; V. Ju. Mokiev (Аграрная наука Евро-Северо-Востока)
In 2017 in the Kirov region the clover-grater-and-scarificator KS-0.2 intended for extraction of seeds from wad of clover and other legumes and grasses as well as scarification of hard legume seeds was investigated. The machine includes frame, body, drum, deck, batch hopper, tedder, device for supplying material to a machine, pipe for input and output, extension, holder for bag, the drive mechanisms, electric equipment. For exception of the operation for deck replacement when reconfiguring the machine it was experimentally investigated the process of scarification of seeds of Galega orientalis with the oval type deck, equipped with 7 steel scarification plates installed between the round bars. Using of methods of mathematical planning of the experiment studied allow to established the influence of constructive and technological parameters on the degree of scarification of seeds and crushing of the seeds. Determined the range of values of the studied parameters under which the observed agro technical requirements for the machine were met. As a result of research defined values are revealed of the constructive and technological parameters of the machine for extraction and scarification grass seed КБ-0.2 with the use of a oval type deck, providing the required quality parameters (degree of scarification of seeds higher than 95% and crushing of seeds less than 1.5%): frequency of rotation of the drum 850...950 min-1; productivity 0.2...0.3 t/h; clearances at the entrance - 6.0 mm, at the outlet - 3.0 mm.